Linguistics Landscapes: New Normal Life Representation in Kuta, Bali - I Wayan Mulyawan; I Gusti Agung Istri Aryani (Program Magister Linguistik Universitas Udayana, 2021)
The covid-19 pandemic has influenced all human life worldwide. This pandemic affects all life in the world, including in Indonesia. Covid-19 had destroyed all aspects of life in Indonesia. One of the most devastating sectors affected is the tourism industry. In order to boost economic sustainability, the Indonesian government, through the Health Ministry, had issued a circular letter no. HK.02.01/MENKES/335/2020 about Protokol Pencegahan Penularan Corona Virus Disease (Covid-19) di Tempat Kerja Sektor Jasa dan Perdagangan (Area Publik) dalam Mendukung Keberlangsungan Usaha [Protocol for Prevention of Corona Virus Disease (Covid-19) Transmission in the Workplace of the Service and Trade Sector (Public Area) in Supporting Business Continuity]. This study is aimed to investigate the implementation of the Covid-19 protocol as an adaptation of New Normal life in Kuta village, Bali, Indonesia. It is chosen as the research area since Kuta is one of the international tourist destinations in Bali that mostly rely on the tourism industry. The data of this study is taken from any outdoor sign representing New Normal protocol in the area. The documentation method and note-taking technique were applied in collecting the data. The analysis is based on linguistics landscapes theory. The result showed that there are 199 outdoors signs found in 10 groups of most tourism facilities. The language of the sign is dominated by the Indonesian language with 84 signs, followed by the combination of English and Indonesian language with 55 signs.